2012
DOI: 10.1377/hlthaff.2011.0922
|View full text |Cite
|
Sign up to set email alerts
|

Half Of Older Americans Seen In Emergency Department In Last Month Of Life; Most Admitted To Hospital, And Many Die There

Abstract: Emergency department use contributes to high end-of-life costs and is potentially burdensome for patients and family members. We examined emergency department use in the last months of life for patients age sixty-five or older who died while enrolled in a longitudinal study of older adults in the period 1992–2006. We found that 51 percent of the 4,158 decedents visited the emergency department in the last month of life, and 75 percent in the last six months of life. Repeat visits were common. A total of 77 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
152
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(171 citation statements)
references
References 34 publications
7
152
0
4
Order By: Relevance
“…Three-month ED use (48%) in this study was similar to rates found in communitydwelling persons approaching the end of life (51%) 36 and far exceeded the 19.1% 1-year ED use found in nationally representative community-dwellers with a similar average age (59.6 years). The cross-sectional design limited our ability to determine the causes of acute care use or anticipated acute care use after release, though in our analysis we included the health, geriatric and social factors that drive acute care use in community-dwelling older adults.…”
supporting
confidence: 74%
“…Three-month ED use (48%) in this study was similar to rates found in communitydwelling persons approaching the end of life (51%) 36 and far exceeded the 19.1% 1-year ED use found in nationally representative community-dwellers with a similar average age (59.6 years). The cross-sectional design limited our ability to determine the causes of acute care use or anticipated acute care use after release, though in our analysis we included the health, geriatric and social factors that drive acute care use in community-dwelling older adults.…”
supporting
confidence: 74%
“…A study of patients older than age 65 years by Smith et al revealed 75% visited an ED in the last 6 months of life and 51% in the last month, many with repeat visits. 3 The transition from curative to noncurative symptom management may greatly change the hospital trajectory of care. Here is the opportunity to initiate further goals of care that may change future plans.…”
Section: • Not Surprisedmentioning
confidence: 99%
“…[3][4][5] Recent research found that half of older Americans visited the emergency department in the last month of life and 75% did so in their last six months of life. 6 While a recent analysis of Medicare beneficiaries found that more people are dying at home with hospice services, hospice length of stay is short because of an increase in hospital and intensive care unit stays in the last month of life that occur before referral to hospice. Further, there has been an increase in the number of people who experience multiple transitions across health care settings near the end of life.…”
Section: Outline Of the Scope Of The Problemmentioning
confidence: 99%